Дезертир: [роман] / А. Валентинов - Валентинов Андрей (Нить времен, 2000)
Экземпляры: (20180823) / Инвентарный номер: 34182 / Цена: 13.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 15 / ББК: 84(2Рос=Рус)6